Effects of a Low Molecular Weight Heparin (Fragmin®) and of Unfractionated Heparin on Coagulation Activation at the Site of Plug Formation In Vivo - Elchinger, Sabine; Wolzt, Michael; Nieszpaur-Los, Malgorzata; Schneider, Barbara; Lechner, Klaus; Eichler, Hans-Georg; Kyrle, Paul A (Thrombosis and Haemostasis, 1994)
The clinical benefits of unfractionated heparin (UFH) and low molecular weight heparin (LMWH) have been shown in many trials. However, the mode of action of heparin has not been fully elucidated. Thus, we wanted to study the effects of UFH and LMWH in vivo by measuring coagulation activation markers in blood obtained directly from a vascular injury site. In a double-blind, randomized, 3-way, cross-over study 18 healthy volunteers were given UFH (150 U/kg s.c.) and 2 doses of LMWH [35 U/kg s.c. (low dose, Id), 75 U/kg s.c. (high dose, hd)]. Prothrombin fragment 1+2 (F1+2), thrombin-antithrombin complex (TAT) and fibrinopeptide A (FPA) were measured in bleeding time blood and in venous blood before and after drug application. In addition, the effects of UFH and LMWH on in vitro coagulation tests were studied. Compared to base line, UFH and both IdLMWH and hdLMWH caused significant reductions of F1+2, TAT and FPA in bleeding time blood at 2 h. A marked effect of UFH and of hdLMWH was also seen at 5 h. The inhibition of FPA generation was more pronounced after hdLMWH compared to IdLMWH. In venous blood, UFH and LMWH caused reductions of F1+2, but not of TAT and FPA. In vitro, UFH predominantly affected the anti-IIa assays (activated partial thromboplastin time, thrombin time) and LMWH mainly the anti-Xa test system. Using a technique that investigates the activated coagulation system in vivo, a time- and dose dependent inhibitory effect of heparin on coagulation activation was detectable. Therefore, in our experimental setting a preferential inhibition of a particular portion of the coagulation system by one of the two heparin preparations was not detectable.